Initiatives endogenes d'intensification et de diversification a l'interieur des agroforets-cacao au Sud-Cameroun: lecons pour une foresterie participative dans les systemes a base de cultures perennes en Afrique centrale et de l'Ouest - Sonwa, D.J.; Weise, Stephan F.; Ndoye, O.; Janssens, M.J.J. (Food and Agriculture Organization of the United Nations, 2003)
Forest cover has deteriorated less in Central Africa than in West Africa. The cocoa cultivation practised in West Africa, after felling of the forest, has contributed to the destruction of that cover. Unlike West Africa, cocoa cultivation in Southern Cameroon (Centaral Africa) is done by smallholders' conversion of the natural forest. This practice today constitutes a factor on which the cocoa farmers rely to counter the fall in the price of cocoa and fluctuations on the international market. In such agroforests, farmer thus manage timber wood, fuelwood, non-wood forest products, etc. by intensification and diversification. By doing so in the cocoa plantations, they attain, within the same ecosystem, the production and conservation objectives. These smallholders forestry practices in the cocoa agroforests are complementary to community forestry recently introduced in Cameroon. The fall in the price and the liberalization of the cocoa line has exposed the economic fragility of the cocoa monoculture systems currently practiced in West Africa. Such lack of economic strength coexist with an economic precariousness shown by low biological diversity, low carbon retention and the emergence of pests, such as capsids. It is therefore now necessary to promote systems with several levels of application, using species that have both ecological and socio-economic functions. The cocoa agroforests of southern Cameroon thus seem to be models that may well be reproduced, with variants, in West Africa during the establishment of new cocoa plantations or the development and/or renewal of existing ones. This paper presents the state of the Central and West African forest resources and proposes recommendations in favour of participatory forestry in the perennial crop-based systems (mainly of cocoa).